1999
DOI: 10.1159/000027907
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Deafness and Viral Infections

Abstract: Sudden deafness is a dramatic and relatively common otological problem. The etiology in most cases remains unresolved although virus involvement has strong support. Sudden deafness has been associated with mumps, rubella, the respiratory and herpes groups of viruses as well as other more rare ones like hantavirus and Lassa virus. Perhaps the bestknown example of virus-induced sudden deafness is acute unilateral hearing loss associated with mumps virus infection. Mumps virus has also been isolated from the inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
0
7
0
1
Order By: Relevance
“…Measles and rubella have also been temporally or serologically associated with a few cases of sudden deafness [13,18] . With widespread immunization against mumps, measles and rubella, the incidence of these diseases has fallen drastically, along with the near eradication of these agents as an etiological agent for ISSHL [19] . However, there has not been a concomitant decline in the incidence of ISSHL, further supporting the argument that these particular viruses are not the cause of most cases of ISSHL.…”
Section: Analysis Of Evidence For and Against The Viral Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Measles and rubella have also been temporally or serologically associated with a few cases of sudden deafness [13,18] . With widespread immunization against mumps, measles and rubella, the incidence of these diseases has fallen drastically, along with the near eradication of these agents as an etiological agent for ISSHL [19] . However, there has not been a concomitant decline in the incidence of ISSHL, further supporting the argument that these particular viruses are not the cause of most cases of ISSHL.…”
Section: Analysis Of Evidence For and Against The Viral Hypothesismentioning
confidence: 99%
“…Other types of viruses such as respiratory viruses, adenovirues and arenaviruses have also been implicated in ISSHL, based on anamnestic or serological data [3,13,19] . On the other hand, some studies have reported lack of increases in antibodies against multiple tested viruses [reviewed by Pitkäranta et al,19 ].…”
Section: Analysis Of Evidence For and Against The Viral Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies, however, reported that mumps virus was only responsible for a very small fraction of ISSHL cases (less than 10%) [7,8], and, measles and rubella virus has been reported as a rare cause of ISSHL serologically in few cases [7,10]. Indeed, these agents, which were considered in the etiology of ISSHL, are almost eradicated thanks to a worldwide vaccination [11].…”
Section: Discussionmentioning
confidence: 99%
“…The cause and pathophysiology of ISSNHL loss remains unclear. The main pathogenic mechanisms are possibly related to vascular disturbances or immunological reactions, perhaps secondary to viral infectons [7–10]. The incidence of ISSNHL is difficult to estimate as spontaneous remission occurs in 70% of the cases [11].…”
Section: Discussionmentioning
confidence: 99%